Hybridity in Bapsi Sidhwa’s an American Brat - Hina Gul,; Rohimmi Noor,; Hardev Kaur Jujar Singh, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
As immigrant fiction continues to emerge from the South Asian diaspora across the globe, theories of gender and identity that mostly treat such novels as bildungsromans are often used to bring to light the plight of literary characters caught between two different cultures. Similar is the case with Bapsi Sidhwa’s An American Brat, which is often read through the lens of the identity crisis that is experienced by Feroza, the protagonist in the novel. Taking Homi K. Bhabha’s concept of hybridity as an analytical tool, however, this essay uses mimicry, ambivalence, and unhomeliness, concepts under hybridity, to facilitate the understanding of Feroza’s experiences in An American Brat. Besides studying if the three selected elements of hybridity can be found in the protagonist, this work also investigates whether or not they are responsible for her decision to choose to stay either in Pakistan or in the United States at the end of the novel.